2020
DOI: 10.2147/jpr.s270689
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Pain on Admission by Level of Cognitive Impairment in Nursing Homes</p>

Abstract: Purpose: To provide contemporary estimates of pain by level of cognitive impairment among US nursing home residents without cancer. Methods: Newly admitted US nursing home residents without cancer assessed with the Minimum Data Set 3.0 at admission (2010-2016) were eligible (n=8,613,080). The Cognitive Function Scale was used to categorize level of cognitive impairment. Self-report or staff-assessed pain was used based on a 5-day look-back period. Estimates of adjusted prevalence ratios (aPR) were derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 41 publications
2
26
2
1
Order By: Relevance
“…Consistent with previous research [ 1 , 3 , 8 , 18 21 ], we showed a lower prevalence of opioid use among residents with higher levels of cognitive impairment or with a diagnosis of dementia. While it is well recognized that pain is often poorly detected among residents who face challenges in expressing and/or communicating their pain symptoms to staff and family [ 1 , 3 , 8 , 18 20 ], this does not fully explain the lower use of opioids evident among residents with dementia across pain strata. There may be a reluctance to use opioids for pain management, even when otherwise indicated, among those with dementia because of concerns about medication risks [ 7 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous research [ 1 , 3 , 8 , 18 21 ], we showed a lower prevalence of opioid use among residents with higher levels of cognitive impairment or with a diagnosis of dementia. While it is well recognized that pain is often poorly detected among residents who face challenges in expressing and/or communicating their pain symptoms to staff and family [ 1 , 3 , 8 , 18 20 ], this does not fully explain the lower use of opioids evident among residents with dementia across pain strata. There may be a reluctance to use opioids for pain management, even when otherwise indicated, among those with dementia because of concerns about medication risks [ 7 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, relatively higher opioid prescribing in LTC may be expected given the high burden of pain in this population [ 1 ]. Prevalence estimates of non-cancer pain among LTC residents range from approximately 25–50%, depending on the study population, pain measure, and time period examined [ 8 11 ]. For some residents in pain, opioids may be an appropriate alternative when other therapies are contraindicated or ineffective [ 12 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this result is that pain is often underreported and underdiagnosed among individuals with cognitive impairment and dementia. 14,15,23…”
Section: Discussionmentioning
confidence: 99%
“… 1 Despite similar frequencies of painful conditions across levels of cognitive impairment, residents with worse cognitive function have decreased pain documented in nursing homes. 2 Among residents with moderate to severe dementia, 45% experienced moderate to severe pain at some point in the previous week. 3 Yet, nursing home direct care staff may fail to recognize pain in residents unable to self-report pain owing to dementia 4 or may confuse indicators of pain with behavioral and psychological symptoms of dementia.…”
Section: Introductionmentioning
confidence: 99%